Pengaruh Kepuasan Pelanggan, Kualitas Pelayanan Dan Experiential Marketing Terhadap Word Of Mouth Media Sosial Instagram (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2016-2017 Pada Pembelian Produk Masker) - Nuraini Nuraini; Agus Widarko; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine Customer Satisfaction, Service Quality and Experiential Marketing of Word of Mouth Instagram Social Media for FEB Unisma Students Force 2016-2017 both partially and simultaneously. This research is expected to provide benefits to companies as additional information in determining the policy to be taken. This type of research uses the postivism paradigm research type using a quantitative approach. This research uses quantitative research. the population in this study were students of FEB Unisma Angkata 2016-2017. Samples taken were 94 respondents. The sampling technique used is purposive sampling. The analytical method used is multiple linear regression analysis that is processed with SPSS 22 software. Data collection methods used are questionnaires and documentation. The results of the study indicate that Customer Satisfaction has a partially significant effect on Word of Mouth. meanwhile Service Quality has a partially significant effect on Word of Mout, and Experiential Marketing has a significant influence on Word of Mouth and Customer Satisfaction, Service Quality and Experiential Marketing have a significant effect simultaneously on Word of Mouth.Keywords: Customer Satisfaction, Service Quality, Experiential Marketing and Word of Mouth.